Smart Agricultural Governance: Methodologically Approached Web Based Automatic Monitoring and Irrigation Using Soil Moisture and Ultrasonic Sensors - Syaifuddin, Ahmad; Saputra, Bagus Dwi; Shodiq, Muhammad (Universitas Muhammadiyah Lamongan, 2024)
Agricultural productivity in Lamongan, particularly in Kedungpring District, is critically challenged by manual land processing and recurring droughts that severely impact chili crop yields. The persistent lack of efficient monitoring and irrigation technologies exacerbates agricultural sustainability concerns. This study aims to develop an automated, IoT-based irrigation management system that optimizes water use efficiency for chili crops through advanced sensor technologies and fuzzy logic processing. Utilizing an ESP8266 microcontroller integrated with soil moisture and ultrasonic sensors, the research employs the Takagi-Sugeno fuzzy logic method to process real-time environmental data. The system dynamically monitors soil moisture levels and water resources, enabling precise irrigation control. Fuzzy calculations generated a solenoid valve operation time of 321 seconds, classified as moderate, demonstrating the methodology's potential for accurate irrigation management. The developed automated monitoring system successfully demonstrates the potential of IoT technologies in addressing agricultural challenges, providing real-time data visualization and intelligent irrigation decision-making. By integrating sensor technologies with fuzzy logic processing, the research offers a promising solution to improve water resource management and potentially enhance crop productivity in drought-prone agricultural regions. Keywords- Fuzzy Methode; Smart Agriculture; Soil Moisture; Takagi-Sugeno; Ultrasonic.